Plant Nutrients and Abiotic Stress Tolerance (Springer Singapore, 2018)
This book discusses many aspects of plant-nutrient-induced abiotic stress tolerance. It consists of 22 informative chapters on the basic role of plant nutrients and the latest research advances in the field of plant nutrients in abiotic stress tolerance as well as their practical applications. Today, plant nutrients are not only considered as food for plants, but also as regulators of numerous physiological processes including stress tolerance. They also interact with a number of biological molecules and signaling cascades. Although research work and review articles on the role of plant nutrients in abiotic stress tolerance have been published in a range of journals, annual reviews and book chapters, to date there has been no comprehensive book on this topic. As such, this timely book is a valuable resource for a wide audience, including plant scientists, agronomists, soil scientists, botanists, molecular biologists and environmental scientists.